Evaluation of land suitability for urban land-use planning: case study Dhaka city - Ullah, Kazi Masel (© 2016 Blackwell Publishing Ltd, 2016)
This article was published in Transactions in GIS [ © 2016 John Wiley & Sons Ltd. ] and the definite version is available at: http://doi.org/10.1111/tgis.12137 The Article's website is at: http://onlinelibrary.wiley.com/doi/10.1111/tgis.12137/abstract